A quantitative ex vivo study of the interactions between reconstituted high-density lipoproteins and human leukocytes. Issue 7 (23rd January 2020) - Pedersbæk, Dennis; Jønsson, Katrine; Madsen, Ditte V.; Weller, Sven; Bohn, Anja B.; Andresen, Thomas L.; Simonsen, Jens B.
Abstract : We used novel quantitative methods to study the interactions between reconstituted high-density lipoproteins (rHDL) and human leukocytes – showing that rHDL cargo are preferentially taken up by monocytes. Abstract : Knowledge of the interactions between nanoparticles and immune cells is required for optimal design of nanoparticle-based drug delivery systems, either when aiming to avoid phagocytic clearance of the nanoparticles or promote an immune response by delivering therapeutic agents to specific immune cells. Several studies have suggested that reconstituted high-density lipoproteins (rHDL) are attractive drug delivery vehicles. However, detailed studies of rHDL interactions with circulating leukocytes are limited. Here, we evaluated the association of discoidal rHDL with leukocytes in human whole blood (HWB) using quantitative approaches. We found that while the rHDL of various lipid compositions associated preferentially with monocytes, the degree of association depended on the lipid composition. However, consistent with the long circulation half-life of rHDL, we show that only a minor fraction of the rHDL associated with the leukocytes. Furthermore, we used three-dimensional fluorescence microscopy and imaging flow cytometry to evaluate the possible internalization of rHDL cargo into the cells, and we show increased internalization of rHDL cargo in monocytes relative to granulocytes. The preferential rHDL association with monocytes and the internalization of rHDL cargo could possibly be mediated by the scavenger receptor class B type 1 (SR-BI), which we show is expressed to a higher extent on monocytes than on the other major leukocyte populations. Our work implies that drug-loaded rHDL can deliver its cargo to monocytes in circulation, which could lead to some off-target effects when using rHDL for systemic drug delivery, or it could pave the way for novel immunotherapeutic treatments aiming to target the monocytes.